Influence of graft thickness on tunnel technique procedures for root coverage: a pilot split-mouth randomized controlled trial - Teodoro de Carvalho, Victor Aguirre (2023)
Objective: To compare the clinical outcomes of the tunnel technique (TUN) combined with either thin connective tissue graft (CTG) (TUN + thin CTG) (1 mm) or thick CTG (TUN + thick CTG) (2 mm) for the treatment of localized gingival recession (GR). Material and methods: Twelve patients, with 24 maxillary localized type RT1 GR were randomly assigned into two groups. Clinical, esthetic, and patient‐reported outcomes were evaluated at baseline and at 6-month follow-up. Results: The TUN + thin CTG group showed a higher mean GR reduction (1.53 ± 0.66) (primary outcome variable) than the TUN + thick CTG group (1.44 ± 0.89), but no statistically significant difference was detected at the 6-month follow-up (p = 0.77). No statistically significant differences were found between TUN + thin CTG and TUN + thick CTG concerning complete root coverage (CRC) (58.3% versus 41.7%, respectively), gingival ticknness (GT) or Root-coverage Esthetic Score (RES) at 6 months. Regarding patient‐reported outcomes, both groups reported having experienced similar pain at 7 days (p > 0.05). No statistically significant differences were found between the groups in the analysis of the aesthetic score. Conclusion: Both treatments showed a similar reduction in GR. In addition, similar CRC, GT, RES, pain and self-reported esthetics were achieved in both groups. Clinical relevance: Application of thin CTG provided a similar result than thick CTG for the treatment of RT1 localized GR.